2022
DOI: 10.1038/s41598-022-17891-9
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effect of Gracilaria gracilis on European seabass gut microbiota community and its functionality

Abstract: Seaweeds are an important source of nutrients and bioactive compounds and have a high potential as health boosters in aquaculture. This study evaluated the effect of dietary inclusion of Gracilaria gracilis biomass or its extract on the European seabass (Dicentrarchus labrax) gut microbial community. Juvenile fish were fed a commercial-like diet with 2.5% or 5% seaweed biomass or 0.35% seaweed extract for 47 days. The gut microbiome was assessed by 16S rRNA amplicon sequencing, and its diversity was not altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 101 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…increased abundance in Vibrio and reduced abundance of Photobacterium ) were previously observed in European sea bass fed with feed supplemented with algal extract (0.35%) but only reduction of Photobacterium abundance has been found when inclusion of algal biomass (2.5% or 5%) in feed 51 . Gonçalves et al 51 interpret the reduction in the abundance of Photobacterium as a limitant for its role as a permanent and latent member of the intestinal microbiota. Specific resistance to infection with Photobacterium damselae subsp.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…increased abundance in Vibrio and reduced abundance of Photobacterium ) were previously observed in European sea bass fed with feed supplemented with algal extract (0.35%) but only reduction of Photobacterium abundance has been found when inclusion of algal biomass (2.5% or 5%) in feed 51 . Gonçalves et al 51 interpret the reduction in the abundance of Photobacterium as a limitant for its role as a permanent and latent member of the intestinal microbiota. Specific resistance to infection with Photobacterium damselae subsp.…”
Section: Discussionmentioning
confidence: 66%
“…This is consistent with meta-analysis of the gut communities of marine fish that revealed that Vibrionales bacteria (which includes the genera Vibrio and Photobacterium ) accounted for 70% of sequence reads 49 , 50 . In European sea bass, many studies were published recently and the overall composition of gut microbiota may significantly vary from a study to another 24 , 51 55 , suggesting that many factors are affecting the gut microbiota composition, such as life stage, sex, season, habitat and diet 50 , 56 , 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is plausible that phytol may have contributed to the intestinal and systemic health of Nile tilapia in the present study. There is currently no comparable study available for comparison, however, the utilization of dietary herbal additives such as thymol [64], common sage, Salvia officinalis [65], and Gracilaria gracilis extract [66], has had a significant impact on the diversity and structure of intestinal bacterial populations in fish.…”
Section: Discussionmentioning
confidence: 99%
“…2006; Boonanuntanasarn et al 2018; Alves Jesus et al 2021). There is no similar study for comparison, but dietary herbal additive supplements, such as thymol (Abd El-Naby et al 2020), common sage, Salvia o cinalis(Hussein et al 2023), and Gracilaria gracilis extract(Gonçalves et al 2022), also changed the diversity and structure of intestinal bacterial population in sh.Glutathione-related antioxidant enzymes, along with direct radical scavenging by GSH, safeguard cells against the harmful effects of oxidative stress caused by excessive reactive oxygen species (Burk and Hill 2010;Liu et al 2019). These antioxidants are often elevated after a stressful event that increases cell respiration and production of superoxide anions that are detoxi ed by superoxide dismutase(Islam et al 2022).…”
mentioning
confidence: 99%